Zinc ion battery, low-concentration hybrid electrolyte for electrochromism and preparation method of low-concentration hybrid electrolyte
By using low-concentration hybrid electrolyte composed of zinc trifluoromethanesulfonate, organic solvent and deionized water in zinc ion batteries and electrochromic devices, the problem of side reactions of electrode/electrolyte interface in low-concentration electrolyte is solved, and efficient electrochemical performance and electrochromic performance are achieved, which is suitable for commercial applications.
Patent Information
- Application Number
- CN202411527142.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-28
AI Technical Summary
Existing zinc ion batteries and electrochromic devices have side reactions in electrode/electrolyte interfaces in low-concentration electrolytes, resulting in zinc negative electrode corrosion, dendrite, hydrogen evolution and other problems, limiting their commercial applications.
A low-concentration hybrid electrolyte composed of zinc trifluoromethanesulfonate, organic solvent and deionized water is used to enter the primary solvated shell of zinc ions through organic solvents and anions to form a specific zinc ion structure, reduce the number of coordination water molecules, and build an anion-based protective layer on the surface of the zinc electrode.
It significantly reduces the side reactions of the electrode/electrolyte interface, improves the specific capacity and cycle stability of zinc ion batteries, and the electrochromic devices achieve efficient color conversion and optical contrast, and the electrolyte is cheap and suitable for commercial production.
Smart Images

Figure CN119542570A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries and electrochromic electrolytes, and in particular relates to zinc ion batteries and low-concentration hybrid electrolytes for electrochromism, and also relates to methods for preparing zinc ion batteries and low-concentration hybrid electrolytes for electrochromism. Background Art
[0002] Metallic zinc has the advantages of being cheap and environmentally friendly, having a low standard electrode potential, a high theoretical specific capacity, and a high hydrogen evolution overpotential. Therefore, secondary zinc-ion aqueous batteries with metallic zinc as the negative electrode are ideal green battery systems with good application prospects in the field of large-scale energy storage. However, side reactions at the electrode / electrolyte interface are the biggest barrier to the commercialization of aqueous zinc-ion batteries. At the positive electrode / electrolyte interface, traditional vanadium-based and manganese-based oxides will slowly dissolve directly or indirectly in the electrolyte, resulting in loss of active materials. At the same time, there is a shuttle effect, which causes uneven deposition of the zinc negative electrode. At the negative electrode / electrolyte interface, zinc corrosion, dendrites, and hydrogen evolution reactions can easily cause battery bloating and short circuits.
[0003] Electrolyte modification is the key to optimizing the electrode / electrolyte interface reaction. In recent years, high-concentration electrolytes have attracted widespread attention. By introducing a large number of zinc ions and anions, the coordination structure of zinc ions and the hydrogen bond network structure in water molecules can be changed, ultimately reducing the number of water molecules in hydrated zinc ions and the activity of free water molecules, thereby inhibiting the electrode / electrolyte interface side reactions. However, high-concentration electrolytes are extremely expensive and have increased viscosity, making them unusable in commercial production. The development of low-cost, low-concentration electrolytes is the only way for aqueous zinc-ion batteries to move towards industrialization. However, in low-concentration electrolytes, electrode / electrolyte side reactions are more serious, mainly involving corrosion, dendrites and hydrogen evolution of the zinc negative electrode, and dissolution and shuttle effects of the vanadium positive electrode. Summary of the Invention
[0004] The present invention aims to provide a zinc ion battery and a low-concentration hybrid electrolyte for electrochromism, which can reduce side reactions at the electrode / electrolyte interface, improve the electrochemical performance of the device, and have low cost and are suitable for commercial applications.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned zinc ion battery and low-concentration hybrid electrolyte for electrochromism.
[0006] The first technical solution adopted by the present invention is that the zinc ion battery and the low-concentration hybrid electrolyte for electrochromism are composed of zinc trifluoromethanesulfonate ((CF3SO3)2Zn), an organic solvent and deionized water.
[0007] The present invention is also characterized in that:
[0008] The organic solvent is one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), triethyl phosphate (TEP), dimethyl sulfoxide (DMSO), ethylene glycol dimethyl ether (DME), dimethylformamide (DMF), and acetonitrile (AN).
[0009] The volume ratio of the organic solvent to the deionized water is 9-1:1, and the concentration of zinc trifluoromethanesulfonate in the mixed solution of the organic solvent and the deionized water is 0.1-1.5 mol / L, wherein the concentration is based on the mixed solution of the organic solvent and the deionized water.
[0010] The second technical solution adopted by the present invention is a method for preparing a zinc ion battery and a low-concentration hybrid electrolyte for electrochromism, comprising the following steps:
[0011] Step 1: At room temperature, weigh a solution in a volume ratio of organic solvent to deionized water of 9 to 1:1 and mix evenly;
[0012] Step 2: Weigh zinc trifluoromethanesulfonate, add zinc trifluoromethanesulfonate to the mixed solution of step 1 and shake to dissolve, so that the concentration of zinc trifluoromethanesulfonate in the mixed solution is 0.1-1.5 mol / L, wherein liter is based on the mixed solution of organic solvent and deionized water only.
[0013] The present invention is also characterized in that:
[0014] In step 1, the organic solvent is one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), triethyl phosphate (TEP), dimethyl sulfoxide (DMSO), ethylene glycol dimethyl ether (DME), dimethylformamide (DMF), and acetonitrile (AN).
[0015] The beneficial effects of the present invention are:
[0016] The zinc ions in traditional low concentration zinc trifluoromethanesulfonate solution are mainly in the form of Zn(H2O)6 2+ The large amount of coordinated H2O is the main factor causing the corrosion of the zinc negative electrode. The addition of organic co-solvents in the electrolyte of the present invention can make itself and the trifluoromethanesulfonic acid anion (OTf - ) enter the primary solvation shell of zinc ions to form Zn(OTf - ) x (Organic) y (H2O) z (2-x)+ (Z<6) structure, which not only reduces the amount of coordinated H2O but also helps to form OTf on the surface of the zinc electrode -The addition ratio of the organic co-solvent is crucial. Only when the addition ratio is greater than or equal to deionized water (that is, the volume ratio of the organic solvent to deionized water specified in the present invention is 9 to 1:1) can a significant effect be achieved. For example, in Example 3 of the present invention, when the volume ratio of acetonitrile to deionized water is 4:1, Zn(OTf - ) 0.81 (AN) 1.78 (H2O) 3.41 1.19+ In addition, the rich O, N, S and F functional groups in the organic solvent will form intermolecular hydrogen bonds with water molecules, reducing the activity of free water molecules, and this effect is only significant when its content is greater than or equal to deionized water. Ultimately, the electrolyte prepared by the present invention can greatly reduce the side reactions at the electrode / electrolyte interface, such as: cathode dissolution and shuttle effect, anode corrosion and dendrites, etc. It can be used in zinc ion batteries at 5Ag -1 It provides about 150 mAh g -1 The specific capacity of the electrolyte (vanadium-based material as the positive electrode, zinc as the negative electrode) was achieved with stable cycling for over 3,000 cycles. Its electrochromic application achieved a brown-red-orange-yellow-green color transition with a maximum optical contrast of 68.2% (vanadium-based material as the electrochromic layer, zinc as the counter electrode). Furthermore, the electrolyte is low-cost, simple to prepare, and suitable for industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is the Fourier transform infrared spectrum of the low-concentration hybrid electrolyte of Example 3 of the present invention;
[0018] Figure 2 This is the molecular dynamics simulation result of the low-concentration hybrid electrolyte of Example 3 of the present invention;
[0019] Figure 3 is the hydrogen evolution and oxygen evolution potential of the low-concentration hybrid electrolyte of Example 3 of the present invention;
[0020] Figure 4 This is the differential thermal spectrum of the low-concentration hybrid electrolyte of Example 3 of the present invention;
[0021] Figure 5 is the UV-visible spectrum of vanadium pentoxide dissolved in the low-concentration hybrid electrolyte of Example 3 of the present invention;
[0022] Figure 6 are the corrosion potential and corrosion current of zinc in the low-concentration hybrid electrolyte of Example 3 of the present invention;
[0023] Figure 7 This is a cycle diagram of a zinc ion battery prepared using the low-concentration hybrid electrolyte of Example 3 of the present invention;
[0024] Figure 8 This is a performance diagram of an electrochromic device prepared using the low-concentration hybrid electrolyte of Example 3 of the present invention. DETAILED DESCRIPTION
[0025] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments.
[0026] The present invention provides a zinc ion battery and a low-concentration hybrid electrolyte for electrochromism, which are composed of zinc trifluoromethanesulfonate ((CF3SO3)2Zn), an organic solvent and deionized water. The organic solvent is one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), triethyl phosphate (TEP), dimethyl sulfoxide (DMSO), ethylene glycol dimethyl ether (DME), dimethylformamide (DMF) and acetonitrile (AN). The volume ratio of the organic solvent to the deionized water is 9 to 1:1. The concentration of the zinc trifluoromethanesulfonate in the mixed solution of the organic solvent and the deionized water is 0.1 to 1.5 mol / L, wherein the liter is calculated based on the mixed solution of the organic solvent and the deionized water.
[0027] The present invention also provides a method for preparing a zinc ion battery and a low-concentration hybrid electrolyte for electrochromism, comprising the following steps:
[0028] Step 1: At room temperature, weigh a solution in a volume ratio of organic solvent to deionized water of 9 to 1:1 and mix evenly;
[0029] In step 1, the organic solvent is one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), triethyl phosphate (TEP), dimethyl sulfoxide (DMSO), ethylene glycol dimethyl ether (DME), dimethylformamide (DMF), and acetonitrile (AN).
[0030] Step 2: Weigh zinc trifluoromethanesulfonate, add zinc trifluoromethanesulfonate to the mixed solution of step 1 and shake to dissolve, so that the concentration of zinc trifluoromethanesulfonate in the mixed solution is 0.1-1.5 mol / L, wherein liter is based on the mixed solution of organic solvent and deionized water only.
[0031] Example 1
[0032] Step 1: At room temperature, weigh 9 ml of acetonitrile and 1 ml of deionized water and mix them evenly.
[0033] Step 2: Weigh 0.36 g of zinc trifluoromethanesulfonate and add it to the mixed solution of step 1, and shake to dissolve.
[0034] Example 2
[0035] Step 1: At room temperature, weigh 5 ml of acetonitrile and 5 ml of deionized water and mix them evenly.
[0036] Step 2: Weigh 5.45 g of zinc trifluoromethanesulfonate and add it to the mixed solution of step 1, and shake to dissolve.
[0037] Example 3
[0038] Step 1: At room temperature, weigh 8 ml of acetonitrile and 2 ml of deionized water and mix them evenly.
[0039] Step 2: Weigh 1.82 g of zinc trifluoromethanesulfonate and add it to the mixed solution of step 1, and shake to dissolve.
[0040] Example 4
[0041] Step 1: At room temperature, weigh 3 ml of ethylene carbonate, 4 ml of propylene carbonate, and 3 ml of deionized water and mix them evenly.
[0042] Step 2: Weigh 3.12 g of zinc trifluoromethanesulfonate and add it to the mixed solution of step 1, and shake to dissolve.
[0043] Example 5
[0044] Step 1: At room temperature, weigh 2 ml of dimethyl carbonate, 2 ml of triethyl phosphate, 2 ml of dimethyl sulfoxide (DMSO), and 4 ml of deionized water and mix them evenly.
[0045] Step 2: Weigh 4.08 g of zinc trifluoromethanesulfonate and add it to the mixed solution of step 1, and shake to dissolve.
[0046] Example 6
[0047] Step 1: At room temperature, weigh 1 ml of ethylene carbonate, 1 ml of propylene carbonate, 1 ml of dimethyl carbonate, 1 ml of triethyl phosphate, 1 ml of dimethyl sulfoxide, 1 ml of ethylene glycol dimethyl ether, 1 ml of dimethylformamide, 1 ml of acetonitrile, and 2 ml of deionized water and mix them evenly.
[0048] Step 2: Weigh 2.36 g of zinc trifluoromethanesulfonate and add it to the mixed solution of step 1, and shake to dissolve.
[0049] Nano sodium vanadate is coated on titanium foil through a binder as the positive electrode, a zinc sheet is used as the negative electrode, and a zinc ion full battery is prepared using the electrolyte prepared by the present invention; vanadium oxide is grown on the surface of conductive glass as the electrochromic layer, and the zinc sheet is used as the counter electrode to prepare an electrochromic device.
[0050] Figure 1 This is the Fourier transform infrared spectrum of the low-concentration hybrid electrolyte of Example 3 of the present invention. Figure 2 This is the molecular dynamics simulation result of the low-concentration hybrid electrolyte of Example 3 of the present invention. Figure 1 and Figure 2It can be seen that the acetonitrile molecules and trifluoromethanesulfonate ions in the low-concentration hybrid electrolyte of Example 3 gradually enter the primary solvation structure of the zinc ion to form Zn(OTf - ) x (AN) y (H2O) z (2-x)+ (Z<6) structure, reducing the number of coordinated water molecules, and finally obtaining the average Zn(OTf - ) 0.81 (AN) 1.78 (H2O) 3.41 1.19+ structure. Figure 3 These are the hydrogen evolution and oxygen evolution potentials of the low-concentration hybrid electrolyte of Example 3 of the present invention. It can be seen that the introduction of acetonitrile can reduce the hydrogen evolution and oxygen evolution side reactions of the electrolyte. Figure 4 This is the differential thermal spectrum of the low-concentration hybrid electrolyte of Example 3 of the present invention. It can be seen that the introduction of acetonitrile can lower the freezing point of the electrolyte. Figure 5 The UV-visible spectra of vanadium pentoxide dissolved in low-concentration hybrid electrolytes of the present invention with different organic to deionized water ratios show that the low-concentration hybrid electrolyte of the present invention has the effect of hindering the dissolution of vanadium pentoxide (zinc ion battery positive electrode material and electrochromic layer), and this is more significant when the organic ratio is greater than or equal to deionized water. Figure 6 These are the corrosion potential and corrosion current of zinc in the low-concentration hybrid electrolyte of Example 3 of the present invention. It can be seen that the introduction of acetonitrile can significantly increase the corrosion potential and reduce the corrosion current, thereby alleviating the side reactions of the zinc negative electrode. Figure 7 The cycle diagram of the zinc ion battery prepared by the low concentration hybrid electrolyte of Example 3 of the present invention is shown in FIG. -1 It provides about 150 mAh g -1 The specific capacity (vanadium-based material as positive electrode, zinc as negative electrode) and stable cycle for more than 3000 cycles. Figure 8 This is a performance diagram of an electrochromic device prepared using the low-concentration hybrid electrolyte of Example 3 of the present invention (vanadium-based material as the color-changing layer, zinc as the counter electrode). It can be seen that it achieves a color transition from brown-red to orange-yellow to green, with a maximum optical contrast of 68.2%.
[0051] In summary, the design principle of the low-concentration hybrid electrolyte of the present invention is: through organic-inorganic hybrid design, a specific organic solvent (with moderate solvation capacity) is selected so that it and the anion enter the primary solvation shell of the zinc ion (such as Figure 1-2 This not only reduces the number of coordinated water molecules, but also builds a protective layer of anionic groups on the surface of the zinc electrode, thereby inhibiting the side reactions of the zinc negative electrode / electrolyte (such as Figure 6In addition, the abundant O, N, S and F functional groups in organic molecules will form intermolecular hydrogen bonds with water molecules, thereby reducing the activity of free water molecules. Ultimately, the hydrogen and oxygen evolution reactions of the electrolyte at low and high pressures are suppressed, and the operating voltage window is widened (e.g. Figure 3 At the same time, this unique design will also inhibit the dissolution of the zinc ion battery positive electrode and electrochromic layer in the aqueous electrolyte (as shown Figure 5 Finally, thanks to the simultaneous protection of the positive electrode (color-changing layer) and the zinc negative electrode by the electrolyte, the electrolyte of the present invention exhibits excellent performance in zinc ion batteries and electrochromic devices.
Claims
1. A zinc ion battery and a low-concentration hybrid electrolyte for electrochromism, characterized in that: It consists of zinc trifluoromethanesulfonate, organic solvent and deionized water.
2. The zinc ion battery and the low-concentration hybrid electrolyte for electrochromism according to claim 1, characterized in that: The organic solvent is one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, triethyl phosphate, dimethyl sulfoxide, ethylene glycol dimethyl ether, dimethylformamide and acetonitrile.
3. The zinc ion battery and the low-concentration hybrid electrolyte for electrochromism according to claim 1, characterized in that: The volume ratio of the organic solvent to deionized water is 9-1:1, and the concentration of zinc trifluoromethanesulfonate in the mixed solution of the organic solvent and deionized water is 0.1-1.5 mol / L, wherein the liter is only based on the mixed solution of the organic solvent and deionized water.
4. A method for preparing a zinc ion battery and a low-concentration hybrid electrolyte for electrochromism, characterized in that: The steps include: Step 1: weigh a solution at room temperature in a volume ratio of 9 to 1:1 of organic solvent to deionized water, and mix them evenly; Step 2, weigh zinc trifluoromethanesulfonate, add the zinc trifluoromethanesulfonate to the mixed solution of step 1 and shake to dissolve, so that the concentration of zinc trifluoromethanesulfonate in the mixed solution is 0.1-1.5 mol / L, wherein liter is only based on the mixed solution of organic solvent and deionized water.
5. The method for preparing a zinc ion battery and a low-concentration hybrid electrolyte for electrochromism according to claim 4, characterized in that: In step 1, the organic solvent is one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, triethyl phosphate, dimethyl sulfoxide, ethylene glycol dimethyl ether, dimethylformamide, and acetonitrile.